GST 2.0 and Its Impact on Economic Growth: A Structural and Macroeconomic Analysis (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
By collapsing the five-tier structure into three slabs (5%, 18%, and 40%), the reform aims to reduce classification disputes and correct inverted duty structures. Using a mixed-method approach—combining secondary data (Q3–Q4 FY2025–26) with sectoral case studies in automobiles, FMCG, and healthcare—this study finds an initial fiscal gap of ₹45,000 crore offset by an 8.1% surge in monthly collections. Econometric projections suggest GST 2.0 contributed to India’s 7.3% GDP growth in FY2026, alongside lower inflation and improved MSME liquidity. Positioned within global VAT/GST experiences, India’s reform illustrates how simplification can stimulate consumption-led growth while raising challenges of fiscal federalism and sin-tax dependency.